Penyelamatan dan Penyelesaian Kredit yang Bermasalah dalam Perjanjian Simpan Pinjam pada Koperasi (Berdasarkan Studi Putusan Nomor 15/Pdt.G/2023/Pn/Mgg) - Sofi A’isy, Alima; Andraini, Fitika (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The case of a simple claim for breach of contract in the Magelang court decision number 15/Pdt.G/2023/PN Mgg was caused by the claim that the peace deed he made was legally flawed and did not have binding legal force. In the process of granting credit, it is in accordance with the 5C credit granting procedure, especially regarding collateral or guarantees, but there is a legal defect in the collateral for mortgage rights whose ownership status is owned by deceased heirs. This research uses normative juridical research with descriptive analysis research methods. Analysis of the Magelang court decision Number 15/Pdt.G/2023/PN Mgg. The results of the research concluded that rescue and settlement of problematic credit was provided after it arose and was resolved in relation to the simple lawsuit decision in the Magelang Court case by filing a simple lawsuit because a simple lawsuit was filed in a case with a material claim value of a maximum of IDR 500 million, namely: breach of contract (default); and/or unlawful acts. In this case, the cooperative filed a lawsuit with the Magelang District Court to obtain a fair decision. Once it is declared rejected in its entirety, the debtor does not compensate for the loss of the lawsuit.